High removal efficiency of industrial toxic compounds through stable catalytic reactivity in water treatment system. (January 2022) - Kim, Soo Hyeon; An, Ha-Rim; Lee, Moonsang; Hong, Yongcheol; Shin, Yongwook; Kim, Hyeran; Kim, ChangYeon; Park, Ji-In; Son, Byoungchul; Jeong, Yesul; Choi, Jong-Soon; Lee, Hyun Uk
Abstract: We identified optimal conditions for the disposal of high concentration of organic contaminants within a short time using a hybrid advanced oxidation process (AOP) combining various oxidizing agents. Plasma-treated water (PTW) containing many active species, that play dominant roles in the degradation of organic substances like hydroxyl radicals, atomic oxygen, ozone, and hydrogen peroxide, was used in this study as a strategy to improve degradation performance without the use of expensive chemical reagents like hydrogen peroxide. In particular, the optimal decomposition conditions using PTW, which were combined with 10 mg/h ozone, 2 g/L iron oxide, and 4 W UV light, demonstrated excellent removal abilities of a high concentration of reactive black 5 (RB5; 100 mg/L, >99%, [k] = 4.15 h −1 ) and tetracycline (TC; 10 mg/L, >96.5%, [k] = 3.35 h −1 ) for 25 min, approximately 1.5 times higher than that without PTW (RB5; 100 mg/L, 94%, [k] = 2.80 h −1 ). These results confirmed that the production of strong reactive hydroxyl radicals from the decomposition process, as well as various reactive species included in PTW efficiently attacked pollutant substances, resulting in a higher removal rate. This suggests that a water treatment system with this optimal condition based on complex AOP systems using PTW could be useful in critical environmental and biomedical applications. Graphical abstract: The water treatment system exhibits higher efficiencies for removal of high-volume organic pollutants. Image 1 Highlights: The optimal conditions of a high-volume water treatment system were investigated. The system exhibits higher efficiency for removal of high-volume organic pollutant. The system can be useful in critical environmental and bio-medical applications.